The study of consumer’s behavior and perception in purchasing rice: case at Jitra, Kedah / Siti Nur Aimi Ahmad - Ahmad, Siti Nur Aimi (Faculty of Plantation and Agrotechnology, 2018)
This research had been conducted to study the factors that affect consumer’s decision in purchasing rice at Jitra, Kedah. Survey questionnaire had been used to gather inputs and feedbacks from 382 identified respondents from mall interception method. The result from the study shows that both factor examine (behavior and perception) give significant in influencing consumer’s decision in purchasing rice by p-value < 0.001.the result also indicate behavior factor show the dominant as compared to perception by beta value 0.478 and 0.438 respectively. Thus, it was concluded that behavior of consumer play an important role in influencing consumer’s purchasing rice especially in Jitra, Kedah.